Structural insights into interactions of C/EBP transcriptional activators with the Taz2 domain of p300. (1st July 2014) - Bhaumik, Prasenjit; Davis, Jamaine; Tropea, Joseph E.; Cherry, Scott; Johnson, Peter F.; Miller, Maria
<x xml:space="preserve">Abstract</x> Members of the C/EBP family of transcription factors bind to the Taz2 domain of p300/CBP and mediate its phosphorylation through the recruitment of specific kinases. Short sequence motifs termed homology boxes A and B, which comprise their minimal transactivation domains (TADs), are conserved between C/EBP activators and are necessary for specific p300/CBP binding. A possible mode of interaction between C/EBP TADs and the p300 Taz2 domain was implied by the crystal structure of a chimeric protein composed of residues 1723–1818 of p300 Taz2 and residues 37–61 of C/EBPɛ. The segment corresponding to the C/EBPɛ TAD forms two orthogonally disposed helices connected by a short linker and interacts with the core structure of Taz2 from a symmetry‐related molecule. It is proposed that other members of the C/EBP family interact with the Taz2 domain in the same manner. The position of the C/EBPɛ peptide on the Taz2 protein interaction surface suggests that the N‐termini of C/EBP proteins are unbound in the C/EBP–p300 Taz2 complex. This observation is in agreement with the known location of the docking site of protein kinase HIPK2 in the C/EBPβ N‐terminus, which associates with the C/EBPβ–p300 complex.